Dynamic generation of superflow in a fermionic ring through phase imprinting - Ke-Ji Chen; Wei Yi; Fan Wu (Physical Review Research)
We study the dynamic generation of persistent current by phase imprinting fermionic atoms in a ring geometry at zero temperature. Mediated by the pairing interaction, the Fermi condensate dynamically acquires a quantized current by developing azimuthal phase slips, as well as density and pairing-order-parameter depletions. Resorting to the Bogolioubov–de Gennes formalism, we investigate the time evolution of the transferred total angular momentum and the quantized superfluid current throughout the phase-imprinting process. This enables a detailed self-consistent analysis of the impact of interaction, as well as different initial pairing states, on the superflow formation, in contrast to previous theoretical analysis based on the Gross-Pitaevskii equation with artificially imposed phases. In particular, we show that, as the interaction strength increases, the azimuthal density distribution becomes less susceptible to the phase imprinting potential, leading to a smaller quantized current under the same imprinting parameters. Our results offer microscopic insights into the dynamic development of superflow in the phase-imprinting process, and are helpful for the ongoing experimental effort.